Polymorphism of HLA-B27 among Ankylosing Spondylitis Patients in Basrah, Iraq - Daekh, Noor Alhuda Karem; Mohammed, Khairallah AS; Ali, Naael Hussein (Scientific Journal of Medical Research, 2020)
Objectives: Ankylosing Spondylitis is an autoinflammatory disease which influence in the sacroiliac joints and the spine lead to damage and inflammation in bones and tendons; this disease associated strongly with gene human leukocyte antigen B27 that infect male more than female. The aim of his study was detect about gene HLAB27 and subtyping for it in AS patients. Methods: in this study, the number of each patients and control were 50 that were from south Iraq which the samples collected during October 2018 to March 2019. The steps of working was involving DNA extraction from whole blood by using ReliaPrep tm Blood g DNA MINIPREP SYSTEM ( Promega, USA); HLAB27 detection by Real time RT-PCR and sequencing for HLAB27 by using primer design. Results: the prevalence of HLAB27 in patients was 72% and in control is 6%, the more prevalence of subtyping was HLAB27:05. Conclusion: : in this study, the prevalence of HLAB27 was 72% in Ankylosing Spondylitis patients and the subtyping were more prevalence of HLAB27 was HLAB27:05.